2021
DOI: 10.1039/d1nr01120k
|View full text |Cite
|
Sign up to set email alerts
|

Janus membrane with novel directional water transport capacity for efficient atmospheric water capture

Abstract: Fresh water scarcity becomes a crisis to human survival and development. Atmospheric water capture with remarkable advantages such as energy-independence, low-cost, etc., has been supposed as a promising way to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Based on our previous research work, we found that for a Janus membrane with asymmetric wettability, once the thickness of the superhydrophilic layer is fixed, the water transport capacity is highly dependent on the thickness of the hydrophobic layer. 14,37,38 Thus, in this work, the thickness of the superhydrophilic TiO 2 @PDA–PLA fabric layer was fixed, and the thickness of the hydrophobic PLA-E fibrous membrane was adjusted based on the electrospinning time. The relationship between the electrospinning time of PLA and the thickness of the Janus membrane is shown in ESI S5.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous research work, we found that for a Janus membrane with asymmetric wettability, once the thickness of the superhydrophilic layer is fixed, the water transport capacity is highly dependent on the thickness of the hydrophobic layer. 14,37,38 Thus, in this work, the thickness of the superhydrophilic TiO 2 @PDA–PLA fabric layer was fixed, and the thickness of the hydrophobic PLA-E fibrous membrane was adjusted based on the electrospinning time. The relationship between the electrospinning time of PLA and the thickness of the Janus membrane is shown in ESI S5.…”
Section: Resultsmentioning
confidence: 99%
“…The single-side deposition of CNTs on the electrospun membrane substrate was achieved, which is difficult to obtain by electrospinning, and the prepared membrane exhibited satisfactory mechanical strength and chemical stability. Additionally, membranes with asymmetric wettability and nanofibers/nanoneedles interpenetrating topology can be fabricated by simple oxidation of copper mesh and electrospinning (Figure c). ,, …”
Section: Fabrication Of Membranes With Asymmetric Wettabilitymentioning
confidence: 99%
“…In addition to the above organisms, inspired by other organisms, some materials with special wettability surfaces or special structures have also achieved excellent results in the field of water collection. [ 21–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above organisms, inspired by other organisms, some materials with special wettability surfaces or special structures have also achieved excellent results in the field of water collection. [21][22][23][24] In order to better understand the principle of water collection of biomimetic materials, the process needs to be understood clearly. Water collection can be divided into three processes: capture of small droplets, water supply, and transport of water.…”
mentioning
confidence: 99%